THE SIGNIFICANCE AND EXPORT POTENTIAL OF SERBIAN ECONOMY WITH SPECIAL REFERENCE TO CONDITION OF LIVESTOCK - Madžar, Lidija (International Journal of Economic Practice and Policy, 2015)
With respect to the availability of significant human and natural resources, as well as the achieved level of production and processing, agriculture is the key economic activity of the Republic of Serbia. However, as a result of the transition process, the agriculture of the Republic of Serbia operates in extremely unstable, unpredictable and unfavorable conditions. It is therefore characterized by an unchanged production structure, primarily in capital-intensive production. Animal Husbandry in Serbia, together with farming, represents an essential branch of the agriculture. Serbian livestock occupies an important place in the national economy because it creates a greatvalue-added by engaging natural and human resources. Although this activity has a chance to grow into a significant agricultural industry, the volume of livestock during the last two decades has been constantly decreasing in the amount of 2-3% per annum. The aim of the research is to examine the causes of the reduced share of national agriculture and livestock in the gross domestic product (GDP) of the country, as well as the cause of the tendency of gradual and persistent reduction and livestock crisis. Data from the paper, for the most part, are based on the Agricultural Census 2012. It should be noted that, due to different definition concepts, data obtained by the latest Census of Agriculture are not fully comparable with the data obtained in the former regular statistical surveys. Census of family farms and farms of entrepreneurs was conducted through interviews. The study also applied statistical analysis methods of current and interval time series data, as well as the method of the considered variables comparison. This paper, first, discusses the importance of agriculture and its foreign trade position in the Serbian national economy. Furthermore, attention is paid to the current state of the domestic livestock and its geographical distribution by statistically defined regions of the Republic of Serbia, whereby the changes of domestic livestock within a period of 18 years are tracked through comparative analysis. Because of the fact that the import of the agricultural products is growing faster than exports, the results indicate that the Republic of Serbia is gradually transformed into a country depending on imports of agricultural products, livestock, meat and dairy products. Extremely unfavorable agricultural policy measures of the Republic of Serbia add to this conclusion.